2006
DOI: 10.1021/bi060769+
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Separate Structural Features That Affect Rate and Cation Concentration Dependence of Self-Cleavage by the Neurospora VS Ribozyme

Abstract: The cleavage site of the Neurospora VS ribozyme is located in an internal loop in a hairpin called stem-loop I. Stem-loop I undergoes a cation-dependent structural change to adopt a conformation, termed shifted, that is required for activity. Using site-directed mutagenesis and kinetic analyses, we show here that the insertion of a single-stranded linker between stem-loop I and the rest of the ribozyme increases the observed self-cleavage rate constant by 2 orders of magnitude without affecting the Mg(2+) requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Initially, we used shiftable SLI substrates with a stable stem Ia (e.g., SLIsb in Figure 1B) as found in the wild-type VS ribozyme, but such SLI variants do not form a stable SLI/SLV complex (not shown), in agreement with biochemical studies showing that stem Ia hinders formation of the I/V kissing-loop interaction. 27,5456 …”
Section: Resultsmentioning
confidence: 99%
“…Initially, we used shiftable SLI substrates with a stable stem Ia (e.g., SLIsb in Figure 1B) as found in the wild-type VS ribozyme, but such SLI variants do not form a stable SLI/SLV complex (not shown), in agreement with biochemical studies showing that stem Ia hinders formation of the I/V kissing-loop interaction. 27,5456 …”
Section: Resultsmentioning
confidence: 99%
“…This may be an example of auxiliary folding elements that are not required for catalysis but appear to assist folding, similar to the loop-loop interaction of the hammerhead (Khvorova et al 2003;Penedo et al 2004) and the four-way junction of the hairpin ribozymes (Murchie et al 1998;Walter et al 1999). In the absence of helix VII, it has been found that increasing the spacing between helices I and II by adding nucleotides leads to faster rates of cleavage (Poon et al 2006), with cleavage occurring at z10 min À1 compared with z0.1 min À1 without the additional linker. In fact, helix I may be physically disconnected from the VS ribozyme with retention of both cleavage (Guo and Collins 1995) (Lafontaine et al 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…The faster rates of cleavage that occur when the constraint on helix I is relieved led Collins and coworkers to propose that in the natural context the VS ribozyme might cleave a physically remote substrate helix within the same transcript (Poon et al 2006). This, in turn, led us to ask whether two fully intact VS ribozymes can undergo a cleavage reaction in trans, whereby helix I of one ribozyme molecule displaces the helix I of the other and docks with it to form a hybrid active site (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The observed rate of RNA cleavage by a given ribozyme can differ by several orders of magnitude depending on which cation is present in the reaction solution (Murray et al 1998;Curtis and Bartel 2001;O'Rear et al 2001;Perrotta and Been 2006;Poon et al 2006;RoychowdhurySaha and Burke 2006). Typically, the observed rate of a cleavage reaction is much faster in divalent than in monovalent ions.…”
Section: Introductionmentioning
confidence: 99%